Professional nurses’ experience in providing nursing care to women experiencing gender-based violence: A caring presence study - Avhatakali Mphephu; Emmerentia du Plessis (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2021)
Background: Women in a sub-district of one of the most rural provinces in South Africa are at a high risk of experiencing gender-based violence. Professional nurses are at the frontline of providing healthcare to these women. Caring presence is a valuable resource to professional nurses in these settings.